Identifying undiagnosed sleep disturbances among self-reported ‘good sleepers’ – future role of community pharmacists? - Mohamad Noor, Zaswiza; Smith, Alesha J.; Nissen, Lisa M.; Smith, Simon S. (2013)
Background: Many people are believed to have normal and adequate sleep, but they may experience undiagnosed sleep disturbances. A low rate of recognition of sleep problems was observed at community healthcare settings. Community pharmacists can play a role to identify and assess sleep quality and quantity through the use of an appropriate validated sleep assessment tool. Early detection may improve sleep conditions and prevent future long-term use of sleep medications. Aim: To identify undiagnosed sleep disturbances in self-reported ‘good sleepers’ using actigraphy. Methods: Individuals (age >18) with no history of sleep-related problems were invited and informed about the study prior to providing informed consent. Each participant was provided with an actigraph (similar to a wrist watch) to be worn for 24-hours/day for 7 consecutive days to record the sleep/wake patterns. After day-7, the actigraph data were downloaded using SleepConsultant™ software to generate an easy to interpret sleep report whilst participants completed a set of questionnaires. Results: Only 43.8% slept for 7-9 hours as recommended, and 75% had an average percentage of sleep efficiency (SE%) below the normal rate of 85%. Those who took longer to fall asleep while in bed also had lower SE%, suggesting that these two measures may be correlated. Conclusions: Using actigraphy to identify and assess sleep/wake patterns in adults is possible to gain early detection of sleep disturbances before the condition worsens. Alongside future actigraphy studies, these findings could support potential new roles for community pharmacists to manage sleep health in individuals who attend the community pharmacy.